Synthesis of chemically diverse esters of 5-aminolevulinic acid for photodynamic therapy via the multicomponent Passerini reaction. Issue 92 (20th September 2016) - Gola, Gabriel F.; Di Venosa, Gabriela M.; Sáenz, Daniel A.; Calvo, Gustavo H.; Cabrera, Gabriela M.; Casas, Adriana G.; Ramírez, Javier A.
Abstract : A chemically diverse set of 5-aminolevulinic acid prodrugs were obtained via a Passerini reaction and studied as photodinamic agents in vitro . Abstract : 5-Aminolevulinic acid-based photodynamic therapy (ALA-PDT) is gaining increasing acceptance in medicine as an effective technique for the treatment of a variety of neoplastic lesions. Unfortunately, the efficacy of ALA-PDT is limited by the hydrophilic nature of the molecule, leading to poor penetration through malignant tissues. This fact prompted the development of more lipophilic ALA derivatives, such as alkyl esters, although this strategy has potential drawbacks, mainly associated with the instability of ALA in solution. In this paper we describe a more versatile methodology for obtaining ALA esters based on the three-component Passerini reaction, which involves mild conditions and a straightforward procedure, allowing efficient generation of chemically diverse libraries of ALA conjugates. The preliminary in vitro evaluation of the new designed compounds allowed us to find a new promising conjugate with enhanced photodynamic properties compared to ALA.